IN SEARCH FOR GENDER EQUALITY IN RURAL MADRASAS OF MALANG RAYA - Hanun Asrohah; Sari Idayatni (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
While gender awareness in the country increasingly arises and is widely debated, few studies have examined the level of gender sensitivity of awareness in Islamic schools. Using case study, this article examines the construction of gender equity in nine rural madrasas in South Malang, Indonesia, by building the framework of social ecosystem of education in madrasas in order to construct the gender equity in rural madrasas. The findings show that in general, the educators in the madrasas already have a gender awareness because they have been familiar with feminism and gender equity in education; however, traditional and conservative gender perspective are still at large. It finds that there are still various gender differences, stereotypes, and an uncomfortable school climate which all challenge the formation of gender equality. Therefore, the social ecosystem of education in rural madrasas deserves enforcement for the embodiment of gender equality.